Corrosion Behavior of Ti-6Al-4V Alloy in Different Media - Majid H. Abdulmageed (Al-Khwarizmi College of Engineering – University of Baghdad, 2010)
In this work the corrosion behavior of Ti-6Al-4V alloy was studied by using galvanostatic measurements at room temperature in different media which includ sodium chloride (food salt), sodium tartrate (presence in jellies, margarine, and sausage casings,etc.), sodium oxalate (presence in fruits, vegetables,etc.), acetic acid (presence in vinegar), phosphoric acid (presence in drink), sodium carbonate (presence in 7up drink,etc.), and sodium hydroxide in order to compare.